2006
DOI: 10.1086/504470
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Magnetic Fields from Large-Scale Structure and Galaxy Cluster Shocks

Abstract: The origin of the micro-Gauss magnetic fields in galaxy clusters is one of the outstanding problem of modern cosmology. We have performed three-dimensional particle-in-cell simulations of the nonrelativistic Weibel instability in an electron-proton plasma, in conditions typical of cosmological shocks. These simulations indicate that cluster fields could have been produced by shocks propagating through the intergalactic medium during the formation of large-scale structure or by shocks within the cluster. The st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 34 publications
(31 reference statements)
2
88
0
Order By: Relevance
“…This prediction has been extended to nonrelativistic shocks, e.g., in supernovae and galaxy clusters (Medvedev et al 2006), and confirmed via numerical particle-in-cell simulations (Silva et al 2003;Nishikawa et al 2003;Frederiksen et al 2004;Medvedev et al 2005;Spitkovsky 2005;Chang et al 2007). The volume-averaged value of B deduced from the simulation is indeed $0.01Y 0.0001 (depending on the location with respect to the main shock compression).…”
Section: Introductionmentioning
confidence: 74%
“…This prediction has been extended to nonrelativistic shocks, e.g., in supernovae and galaxy clusters (Medvedev et al 2006), and confirmed via numerical particle-in-cell simulations (Silva et al 2003;Nishikawa et al 2003;Frederiksen et al 2004;Medvedev et al 2005;Spitkovsky 2005;Chang et al 2007). The volume-averaged value of B deduced from the simulation is indeed $0.01Y 0.0001 (depending on the location with respect to the main shock compression).…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, since cosmic-ray acceleration and generation of galactic magnetic field are directly related to the amount of shocked gas Keshet et al 2003;Medvedev et al 2006;Pavlidou & Fields 2006), our formalism can also be applied to compute these processes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…At the same time, the existence of diffuse synchrotron emission at radio wavelengths and Faraday rotation measurements indicate the presence of magnetic fields in galaxy clusters with strengths up to tens of microgausses (4,5). The standard model for the origin of these intergalactic magnetic fields is amplification of seed fields via the turbulent dynamo mechanism to the present-day observed values (6-10), but other possibilities involving plasma kinetic instabilities (11)(12)(13)(14), return currents (15,16), or primordial mechanisms (17,18) have also been invoked.…”
mentioning
confidence: 99%